REGULATION OF ACIDIC AND BASIC TYPES OF PROTEINS OF A TELEOST TIL API A MOSSAMBICA UNDER SUBLETHAL MALATHION IMPACT - Sahib, I Kabeer Ahammad; Rao, K Siva Prasada; Rao, K R S Sambasiva; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
During the course of malathion (2mg/l) exposure, the sucrose-soluble proteins and insoluble proteins increased considerably in muscle, gill and liver tissues throughout the time course study. The acidic and basic types of protein also showed an increase in muscle, gill and liver tissues. With some exception, in all the time intervals, the basic type of protein was relatively higher than the acidic type of protein leading to basic intracellular enviornment. In spite of less effectiveness of malathion in basic environment, the higher levels of basic proteins may partially contribute towards detoxification. It is likely that an effective buffering potential may exist in the malathion exposed fishes, probably regulated by controlled synthesis of acidic and basic types of protein